2023
DOI: 10.1038/s41467-023-42679-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin of fungal hybrids with pathogenic potential from warm seawater environments

Valentina del Olmo,
Verónica Mixão,
Rashmi Fotedar
et al.

Abstract: Hybridisation is a common event in yeasts often leading to genomic variability and adaptation. The yeast Candida orthopsilosis is a human-associated opportunistic pathogen belonging to the Candida parapsilosis species complex. Most C. orthopsilosis clinical isolates are hybrids resulting from at least four independent crosses between two parental lineages, of which only one has been identified. The rare presence or total absence of parentals amongst clinical isolates is hypothesised to be a consequence of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…to not have access to sexual reproduction 116 . Even fungal pathogens evolve through recurrent hybridization events 28,97,[117][118][119][120][121] and acquire antifungal resistance and adapt to new hosts with de novo mutations and LOH [122][123][124][125][126] . It has indeed been shown that to confer full resistance to antifungals, a mutation in a transcriptional regulator needed to be followed by LOH 127 .…”
Section: Discussionmentioning
confidence: 99%
“…to not have access to sexual reproduction 116 . Even fungal pathogens evolve through recurrent hybridization events 28,97,[117][118][119][120][121] and acquire antifungal resistance and adapt to new hosts with de novo mutations and LOH [122][123][124][125][126] . It has indeed been shown that to confer full resistance to antifungals, a mutation in a transcriptional regulator needed to be followed by LOH 127 .…”
Section: Discussionmentioning
confidence: 99%
“…The second used proxy, rAUC, was defined as area under the log2 drug concentration-vs-AUC, normalized by the maximum AUCMAX where there is no change in growth across all the tested concentrations. For a validation of the agar-based method described here by comparison with a liquid-based method, refer to Del Olmo et al. (2023) and Mixão et al.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, hybrids may survive, and their characteristic genomic plasticity may confer them some advantages, including the ability to survive in new environments (1, 5). Over the last years, a growing number of yeast hybrid lineages have been described (6), and hybridization has been hypothesized as a possible mechanism leading to the emergence of new pathogens, as it is the case of Candida orthopsilosis, Candida metapsilosis, Candida inconspicua, Candida tropicalis or even Candida albicans (1, 715).…”
Section: Introductionmentioning
confidence: 99%